Liability for Shareholders and Directors of Limited Liability Companies, for CSR-Related Breaches - Margrethe Buskerud Christoffersen (Oslo Law Review, 2024)
If a limited liability company does not comply with its obligations, the directors and the shareholders of the company can be held liable on further terms under Norwegian law. Such liability can be based on section 17-1 of the Limited Liability Company Act, and the shareholders can additionally be held liable based on the doctrine of piercing the corporate veil. There are several statutes that impose obligations on companies related to human rights, climate and the environment, and if directors or shareholders have acted negligently, they can be held liable for third partiesʼ loss suffered as a result of the companyʼs lack of fulfilment of its obligations. The directors may also be liable for compensatory losses suffered as a result of failure to safeguard the companyʼs interests. Societal interests are part of the companyʼs interest, but there are no examples in Norwegian law of board members being held liable for failure to safeguard such interests.